Study of Nonlinear Refraction and Nonlinear Absorption Coefficients of Different CdS Film Thickness by diode laser (Baghdad Science Journal, 2013)
In the present work, different thicknesses of CdS film were prepared by chemical bath deposition. Z-Scan technique was used to study the nonlinear refractive index and nonlinear absorption coefficients. Linear optical testing were done such as transmission test, and thickness of films were done by the interference fringes (Michelson interferometer). Z-scan experiment was performed at 650nm using CW diode laser and at 532nm wavelength. The results show the effect of self-focusing and defocusing that corresponds with nonlinear refraction n2. The effect of two-photon absorption was also studied, which correspond to the nonlinear absorption coefficient B.